Modern Arts of the Qur’an and its Aesthetic Reception of the Qur’anic Marble Inscription in Indonesia - Shinta Nurani; Luthfi Maulana (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This article explores the aesthetic reception of the modern marble inscription of the Qur'an and its underlying meaning. The study uses field research and locates its research locus at Masjid Al-Muhtaram, Kajen, Pekalongan Regency where the marble stone is kept. The research adopts Wolfgang Iser's reception theory to analyse the meaning of the marble stone Al-Qur'an from an aesthetic standpoint. The results show that the marble stone inscription of the Qur'an was made by Nur Hidayat Siba, starting in 2011 until 2021, and has reached 13 juz of the Qur'an. The marble measures 60 x 90 cm with a thickness of 2 cm, and is written with beautiful khat and gold colour wrapping on every khat. The inscription provides three meanings of aesthetic reception. Firstly, the objective meaning of the Qur'an as a holy book must be preserved through beautiful media as a form of appreciation for the greatness of the Qur'an. Secondly, the expressive meaning is used as a medium of Islamic da'wa, and spirituality increases faith and religious aspects for those who see and read it. Finally, the meaning of documentary serves as a form of habitus to always interact with the Qur'an in everyday life. These three meanings illustrate the diversity of meanings in the aesthetic reception of the marble Al-Qur'an. The study contributes to the body of knowledge by shedding light on the significance of aesthetic reception of the Qur'an and highlights the importance of preserving the holy book through beautiful media.